2006
DOI: 10.1108/07363760610712993
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction and loyalty in a digital environment: an empirical test

Abstract: Purpose -The purpose of this paper is to explore the links between customer loyalty attitude, customer loyalty behaviours (measured by customer purchase behaviours) and profitability. The aim is to define a conceptual framework within which to analyse the relationships between attitudes, behaviour, and profitability of the customers. Design/methodology/approach -Reference was made to earlier studies which argued that loyal customers constitute competitive asset of business organizations. Several authors noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 93 publications
3
83
1
3
Order By: Relevance
“…Kim, et al, 2008). Trust has also been found to positively affect consumers' purchase intentions towards a specific web site store (Chang & Chen, 2008;Donio', Massari, & Passiante, 2006). Further investigation supported the view that e-loyalty was significantly and positively influenced by e-trust (Floh & Treiblmaier, 2006;Horppu, et al, 2008;Jin, et al, 2008).…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 63%
See 1 more Smart Citation
“…Kim, et al, 2008). Trust has also been found to positively affect consumers' purchase intentions towards a specific web site store (Chang & Chen, 2008;Donio', Massari, & Passiante, 2006). Further investigation supported the view that e-loyalty was significantly and positively influenced by e-trust (Floh & Treiblmaier, 2006;Horppu, et al, 2008;Jin, et al, 2008).…”
Section: Theoretical Framework and Hypothesessupporting
confidence: 63%
“…Others found that both trust and commitment were positively and significantly associated with purchase behaviour (Donio', et al, 2006;Park & Kim, 2003).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…It is also defined as positive influence on the desire to keep the relationship with service firm alive and well (Komunda & Osarenkhoe, 2012). Thus, the attitudinal loyalty is an indication of the behavioral side of customer loyalty (Donio, Massari, and Passiante, 2006), and it helps in reducing the switching behavior (Caceres & Paparoidamis, 2007).…”
Section: A Attitudinal Loyalty (Acl)mentioning
confidence: 99%
“…Studies found several positive outcomes of e-CRM performance such as customer satisfaction [14,17], purchase intentions [14,29], customer retention [13], knowledge management [8], profitability [15], relationship development [25], organizational commitment [20; 29] and customer loyalty [16; 4].…”
Section: Literature Reviewmentioning
confidence: 99%